2007
DOI: 10.1007/s11030-007-9061-9
|View full text |Cite
|
Sign up to set email alerts
|

Efficient synthesis of alkyl 2-[2-(arylcarbonylimino)-3-aryl-4-oxo-1, 3-thiazolan-5-ylidene]-acetates

Abstract: Reaction of 1-aryl-3-arylcarbonylthioureas with dialkyl acetylenedicarboxylates in CH(2)Cl(2) at room temperature leads to alkyl 2-[2-(arylcarbonylimino)-3-aryl-4-oxo-1,3-thiazolan-5-ylidene]-acetates in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…On the basis of well established chemistry of electrophilic acetylenes [10], it is reasonable to assume that the synthesis proceeds through initial conjugate addition of the sulfur atom of 1 onto the acetylenic ester following cyclocondensation of the thus formed 1:1 adduct [13,14] to yield the products 3 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of well established chemistry of electrophilic acetylenes [10], it is reasonable to assume that the synthesis proceeds through initial conjugate addition of the sulfur atom of 1 onto the acetylenic ester following cyclocondensation of the thus formed 1:1 adduct [13,14] to yield the products 3 (Scheme 3).…”
Section: Resultsmentioning
confidence: 99%
“…Several substituted thiazolidinones have been found to possess hypnotic, anesthetic, sedative, anticonvulsant, and microbiological activities [2][3][4]. Some thiazoline derivatives show interesting anti-HIV or anticancer activities and can inhibit cell division [5][6][7][8][9][10]. Because of the various physiological activities of thiazolidinones, many thiazolidinone derivatives have been prepared and several new methods for the preparation of substituted thiazolidine-4-one have been recently reported [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Yavari et al , reported the preparation of alkyl 2‐[2‐(aryl carbonylimino)‐3‐aryl‐4‐oxo‐1,3‐thiazolan‐5‐yiel‐dne]acetates 124a , 124b , 124c , 124d , 124e , 124f , 124g , 124h , 124i , 124j , 124k , 124l , 124m via the reactions between 1‐ary‐3‐aryl carbonylthioureas 123a , 123b , 123c , 123d , 123e , 123f , 123g , 123h , 123i , 123j , 123k and dialkyl acetyl‐enedicarboxylates 1a , 1b in dichloromethane at ambient temperature (Scheme ).…”
Section: Chemistry Of Dimethyl Acetylenedicarboxylatementioning
confidence: 99%
“…The literatures on reactions of hydrazine‐carbothioamides with dialkyl acetylenedicarboxylates contain contradiction in the structure of heterocycles obtained from structurally similar thiocarbonyl substrates . These differences could be attributed to solvent effect, effects condition, and to electronic or structural environment .…”
Section: Introductionmentioning
confidence: 99%